Improving Animal Welfare in Shelter Environments in Northern Cyprus - Tarhun, Laden; Muhy Al-Din, Salar Salah; Damgaci, Ahenk Yilgin (Journal of Salutogenic Architecture, 2024)
Animal shelters are facilities established to meet the shelter needs of animals that have no home or have been abandoned by their owners. Animal shelters in contemporary aim to provide homeless animals with a temporary house and at the same time try to help feed them and healthily care for them. The continuously growing animal population in Northern Cyprus highlights the importance of animal shelter design and operational aspects for animal well-being. Drawing on interdisciplinary principles from interior design, spatial quality, and animal psychology, the study aims to transform shelters from confinement spaces into environments that promote long-term welfare. Using a qualitative, interpretive approach, the research conducts a systematic review of existing literature to analyze shelter conditions, human-animal interactions, and spatial dynamics in current facilities. The implications of this study are expected to make a valuable contribution to the development of design principles and standards that target the improvement of both the physical and psychological living conditions in animal shelters. The goal of the study is to maximize the current state of shelter conditions and lead the way in maximizing animal welfare. These principles aim to provide real solutions to reduce the stress of animals in animal shelters in North Cyprus, to increase adoption rates, and more importantly to develop a humane shelter system. Through the systematic examination of these overlooked concerns, the present study substantially enhances the welfare of animals in shelters while simultaneously optimizing the efficacy of the animal care methodologies.